Efficacy and safety of lomitapide in familial chylomicronaemia syndrome. (October 2022) - Cefalù, Angelo B.; D'Erasmo, Laura; Iannuzzo, Gabriella; Noto, Davide; Giammanco, Antonina; Montali, Anna; Zambon, Alberto; Forte, Francesco; Suppressa, Patrizia; Giannini, Stefano; Barbagallo, Carlo M.; Ganci, Antonina; et al.
Abstract: Background and aims: Familial chylomicronaemia syndrome (FCS) is a rare autosomal recessive disorder, resulting in elevated triglycerides (TGs), abdominal pain and pancreatitis. Treatment options are limited. Lomitapide, a microsomal triglyceride transfer protein inhibitor, is approved for the treatment of homozygous familial hypercholesterolaemia. Whether its therapeutic use may be extended to FCS remains unknown. The aim of this study was to evaluate the efficacy and safety of lomitapide in adult patients with FCS. Methods: The open-label, single-arm 'LOCHNES' study of lomitapide in FCS enrolled patients >18 years with genetically confirmed FCS, elevated fasting TG ≥ 750 mg/dL and history of pancreatitis. Patients were administered lomitapide to the maximum tolerated dose for 26 weeks. The primary endpoint was the percent change in TGs from baseline to Week 26. Results: Eighteen patients were enrolled with median baseline TG levels 1803.5 mg/dL (97.5% CI, 1452–2391 mg/dL). At Week 26, median fasting TGs were reduced to 305 mg/dL (97.5% CI 219–801 mg/dL; 70.5% reduction); median lomitapide dose was 35 mg/day; 13 patients achieved TGs ≤750 mg/dL. Adverse events were mild to moderate and mainly related to gastrointestinal tolerability. Liver imaging at baseline and Week 26 revealed hepatic fat increases from median 12.0%–32.5%, while median hepatic stiffness remained normal. No patient experienced acute pancreatitis or severe abdominal pain during lomitapide treatment. Conclusions: Lomitapide is effective and well tolerated in reducing TGs in FCS patients with a history of pancreatitis. Larger studies are warranted to determine lomitapide effectiveness in FCS. Graphical abstract: Image 1 Highlights: The severe hypertriglyceridemia of familial chylomicronaemia syndrome (FCS) causes pancreatitis. Lomitapide was evaluated in genetically confirmed FCS with prior pancreatitis. Triglycerides were reduced by 70.5% to median 305 mg/dL versus baseline at 26 weeks. Most (13 of 18) patients achieved triglycerides ≤750 mg/dL at 26 weeks. Lomitapide was generally well tolerated and no patients discontinued the study